2009
DOI: 10.1021/ja809816x
|View full text |Cite
|
Sign up to set email alerts
|

Using a Hydrazone-Protected Benzenediazonium Salt to Introduce a Near-Monolayer of Benzaldehyde on Glassy Carbon Surfaces

Abstract: A methodology is described for introducing a thin layer of covalently attached benzaldehyde on glassy carbon surfaces using aryl diazonium chemistry. Usually the electroreduction of aryl diazonium salts leads to the formation of an ill-defined multilayer because of the involvement of highly reactive aryl radicals that can add to already-grafted aryl groups. However, in this study we used a two-step "formation-degradation" procedure to solve this problem with the first step consisting of an electrografting of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 67 publications
3
68
0
Order By: Relevance
“…The second method described as a ''formation-degradation'' process allows via the electrochemical grafting to fabricate monolayer or thin film on the electrodes with anchoring functions. Indeed, this was realized by cleavage of the protecting reactive group (such as a diaryl disulfide [23], a hydrazone group [24] or a function [25,26]) inside the thick electrografted film that remove the multilayer films and give free function (a thiol, an aldehyde or an ethynyl function were respectively obtained after electrochemical oxidation, acid hydrolysis or ammonium fluoride) for post-functionalization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The second method described as a ''formation-degradation'' process allows via the electrochemical grafting to fabricate monolayer or thin film on the electrodes with anchoring functions. Indeed, this was realized by cleavage of the protecting reactive group (such as a diaryl disulfide [23], a hydrazone group [24] or a function [25,26]) inside the thick electrografted film that remove the multilayer films and give free function (a thiol, an aldehyde or an ethynyl function were respectively obtained after electrochemical oxidation, acid hydrolysis or ammonium fluoride) for post-functionalization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In many technological applications, robust surface coatings that are resistant to harsh environments are a prerequisite, and an alternative way to prepare robust surface layers is to covalently bind functional groups on conducting surfaces by electrografting via electrochemical reduction of aryl diazonium salts [31] and aryl iodonium salts [32][33][34]. This technique has been applied to immobilize various functional groups such as alkylamine, thiophenolates, hydroxy and aldehydes [35,36] on surfaces such as glassy carbon (GC) [33,34] and metal oxides [37]. It has been shown that under certain conditions, aryl films formed from reduction of diazonium salts are even more strongly bound to gold surfaces than the thiol analogues [38].…”
Section: Introductionmentioning
confidence: 99%
“…However, an undesirable counterback is the chemical inertness of these molecules, which precludes further functionalization. To remedy this problem, aryldiazonium salts bearing a pendant function masked by a protecting group exhibiting steric hinderance [28][29][30][31] and electronic shielding 29 properties have been used (Fig. 1d).…”
mentioning
confidence: 99%